Fluid-related Earthquake Swarms at East Java Forearc - Anne Sirait; Iman Fatchurochman (Jurnal Geosains Terapan, 2022)
In this study, seismicity along the Java margin was analyzed to identify earthquake swarms. An earthquake swarm was identified in the year 2018. The 2018 earthquake swarm off eastern Java was in the subducting plate rather than on the subducting plate. We manually picked the P-phase arrival times and waveforms were cross-correlated to identify families of events in a swarm. Analysis of the spatio-temporal distribution of families of events in swarms indicated they were fluid-related. The earthquake swarm off eastern Java appears to be associated with over-pressured fluid trapped by impermeable rocks. The existence of this swarm is indicative of the origin of the swarm other than slow-slip events on the plate interface. The identification of earthquake swarms in this study reveals an origin of swarms other than the plate interface.